Figure Concept and Method - Lury, Celia; Viney, William; Wark, Scott (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This open access book shows how figures, figuring, and configuration are used to understand complex, contemporary problems. Figures are images, numbers, diagrams, data and datasets, turns-of-phrase, and representations. Contributors reflect on the history of figures as they have transformed disciplines and fields of study, and how methods of figuring and configuring have been integral to practices of description, computation, creation, criticism and political action. They do this by following figures across fields of social science, medicine, art, literature, media, politics, philosophy, history, anthropology, and science and technology studies. Readers will encounter figures as various as #jesuischarlie, #MeToo, social media personae, gardeners, asthmatic children, systems configuration management and cloud computing. Each chapter demonstrates the methodological utility and contemporary relevance of thinking with figures. This book serves as a critical guide to a world of figures and a creative invitation to "go figure!" Celia Lury is Professor in the Centre for Interdisciplinary Methodologies, University of Warwick. She has a long-standing interest in the ways in which "live" methods contribute to the enactment of social worlds. Her most recent book is Problem Spaces: How and Why Methodology Matters (2020). William Viney is a research fellow in the Department of Anthropology, Goldsmiths, University of London, as part of the project "People Like You": Contemporary Figures of Personalisation. His most recent book is Twins: Superstitions and Marvels, Fantasies and Experiments (2021). Scott Wark is a research fellow for the Wellcome-funded project, "People Like You": Contemporary Figures of Personalisation. He is based at the Centre for Interdisciplinary Methodologies at the University of Warwick. His main research focus is on online culture.